JOGORKU KENESH AND POLITICAL PARTIES OF KYRGYZSTAN: INTERACTION IN PARLIAMENTARY FORM OF GOVERNMENT - Arabaev R.,; Berenalieva A., (Scientific Journal of Pedagogy and Economics, 2021)
The article analyzes using the normative and systematic methods, as well as analysis and synthesis, the content of the statements of the Constitution of the Kyrgyz Republic, the Constitutional Law of the Kyrgyz Republic “On Election of the President of the Kyrgyz Republic and Deputies of the Jogorku Kenesh of the Kyrgyz Republic”, the Laws of the Kyrgyz Republic “On Regulations of the Jogorku Kenesh of the Kyrgyz Republic» and «On the Status of a Deputy of the Jogorku Kenesh of the Kyrgyz Republic» and the works of legal scholars. The study analyzes the issues of interaction between political parties and the Jogorku Kenesh – the parliament of the Kyrgyz Republic in parliamentary form of government. The authors consider the transformation of Kyrgyzstan into a parliamentary republic as a native process, justify the conditioning of the increasing role of political parties in formation of the Jogorku Kenesh and organization of its activities with the signs and requirements of this form of government. Particular attention is paid to the party-political and constitutional-legal foundations of mutual influence of the parliament and political parties of the Kyrgyz Republic. Researchers came to the conclusion the transformation of modern Kyrgyzstan into a parliamentary republic leads to a significant increase in the role of political parties both in the formation of the Jogorku Kenesh and in the organization of its activities as a whole; the interaction of the Jogorku Kenesh and political parties in the parliamentary form of government, in particular, is manifested in the organization and conduct of elections of deputies of the Jogorku Kenesh, distribution of deputy mandates, formation of parliamentary fractions and organization of their activities, determination of the organizational structure of the Jogorku Kenesh and formation of its bodies and organization of parliamentary activities in whole. From the point of view of the authors the fact that mutual relations between the Jogorku Kenesh and political parties are based on legal principles and norms, this whole process takes place on political plane and is sent implementing party programs.